Pityriasis Rosea in a Woman and Her Husband - Case Report and Review of the Literature - Natalya Lemster; Michal Neumark; Arieh Ingber (Karger Publishers, 2010)
Pityriasis rosea is an acute, self-limited papulosquamous dermatosis of the trunk and extremities. Many atypical forms of the disease have been reported in the literature [Ahmed et al.: Clin Exp Dermatol 2000;25:624-626; Imamura et al.: Dermatologica 1985;171:474-477]. It is rare to find pityriasis rosea in multiple family members (within a household) at the same time. There have been only 4 reported cases where a couple has contracted pityriasis rosea simultaneously [Miller et al.: Arch Derm Syphilol 1941;44:66-68; Niles et al.: Arch Derm Syphilol 1940;41:264].